1998
DOI: 10.1111/j.1752-1688.1998.tb00952.x
|View full text |Cite
|
Sign up to set email alerts
|

HYDROLOGIC CALIBRATION OF THE SWAT MODEL IN A WATERSHED CONTAINING FRAGIPAN SOILS1

Abstract: The Soil and Water Assessment Tool (SWAT) model, designed for use on rural ungaged basins and incorporating a GRASS GIS interface, was used to model the hydrologic response of the Ariel Creek watershed of northeastern Pennsylvania. Model evaluation of daily flow prior to calibration revealed a deviation of runoff volumes (Dy) of 68.3 percent and a Nash-Sutcliffe coefficient of -0.03. Model performance was affected by unusually large observed snowmelt events and the inability of the model to accurately simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 12 publications
3
78
0
6
Order By: Relevance
“…Dentre os muitos modelos que tentam exprimir a ação dos principais fatores que exercem influência nas perdas de solo pela erosão hídrica, estão os modelos conceituais distribuídos que simulam os diversos processos no ciclo hidrossedimentológico. Um desses modelos é o Soil and Water Assessment Tool (SWAT), que permite uma grande flexibilidade na configuração de bacias hidrográficas (Peterson & Hamlett, 1998). O modelo foi desenvolvido para predizer o efeito de diferentes cenários de manejo na qualidade da água, produção de sedimentos e cargas de poluentes em bacia hidrográficas agrícolas (Srinivasan & Arnold, 1994).…”
Section: Introductionunclassified
“…Dentre os muitos modelos que tentam exprimir a ação dos principais fatores que exercem influência nas perdas de solo pela erosão hídrica, estão os modelos conceituais distribuídos que simulam os diversos processos no ciclo hidrossedimentológico. Um desses modelos é o Soil and Water Assessment Tool (SWAT), que permite uma grande flexibilidade na configuração de bacias hidrográficas (Peterson & Hamlett, 1998). O modelo foi desenvolvido para predizer o efeito de diferentes cenários de manejo na qualidade da água, produção de sedimentos e cargas de poluentes em bacia hidrográficas agrícolas (Srinivasan & Arnold, 1994).…”
Section: Introductionunclassified
“…They evaluated SWAT's ability to simulate low flow conditions that included snow-melt events. Chanasyk et al (2003) and Peterson and Hamlet (1998) found that SWAT was better suited for long simulation periods and suggested that the snowmelt routine be improved. The modifications performed by Fontaine et al (2002) …”
Section: Snowmelt-related Applicationsmentioning
confidence: 99%
“…1) not for simulating sub-daily events such as a single storm event and diurnal changes of dissolved oxygen in a water body; 2) only route one pesticide each time through the stream network; 3) can not specify actual areas to apply fertilisers; 4) a large watershed can be divided into hundreds of hydrologic response units (HRU) resulting in many hundreds of input files, which are difficult to manage and modify without a solid interface; 5) the parameters of the equations are not directly measured by using data; 6) it has the difficulty in simulating snowmelt; 7) it does not simulate detailed event based flood and sediment routing; 8) it has difficulties in modelling floodplain erosion and snowmelt erosion during the spring and winter months (Peterson and Hamlett 1998;Benaman et al, 2005;Shoemaker et al, 2005). Although efforts have been made to incorporate more process-based equations, some of the basic processes modelled by SWAT still have room for improvement.…”
Section: Model Descriptionmentioning
confidence: 99%